2013
DOI: 10.1002/nbm.2922
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral substantia nigra and pyramidal tract changes following experimental intracerebral hemorrhage: an MR diffusion tensor imaging study

Abstract: The amelioration of secondary neurological damage is among the most important therapeutic goals for patients with intracerebral hemorrhage (ICH). Secondary injury of the ipsilateral substantia nigra (SN) and pyramidal tract (PY) is common after cerebral stroke. Such injury has been characterized previously by anatomical or diffusion MRI, but not in a comprehensive manner, and the knowledge regarding the contralateral changes is relatively poor. This study examined longitudinally both contralateral and ipsilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…DTI/MRI has been investigated as a promising technique to evaluate functional outcome and compare treatment effects in patients with ICH37. Only a few preclinical ICH studies have used FA to estimate white matter injury and repair181938. The first study showed decreased FA value at day 3 together with histologically determined neuronal degeneration, which continued to 120 days after collagenase-induced ICH in rats18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DTI/MRI has been investigated as a promising technique to evaluate functional outcome and compare treatment effects in patients with ICH37. Only a few preclinical ICH studies have used FA to estimate white matter injury and repair181938. The first study showed decreased FA value at day 3 together with histologically determined neuronal degeneration, which continued to 120 days after collagenase-induced ICH in rats18.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few preclinical ICH studies have used FA to estimate white matter injury and repair181938. The first study showed decreased FA value at day 3 together with histologically determined neuronal degeneration, which continued to 120 days after collagenase-induced ICH in rats18. The second study, which used the blood-injection ICH model in rats, also showed a decrease in FA in the tissue near the haemorrhagic region on days 1 and 3 but did not present longer-term data38.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In densely packed white matter bundles, axonal membranes and myelination both contribute to FA, with the former arguably producing a greater contribution [49]. Focal ischemia models have correlated FA reductions with both axonal loss and demyelination [50, 51]. More generally following tissue damage, and particularly in gray matter, several studies have cautioned against interpreting FA as a simple combination of axonal density and white matter myelination.…”
Section: Structural Connectivity: Imaging Of White Matter By Diffusiomentioning
confidence: 99%
“…Shu-Jan Fan et al suggest that our poor understanding of the contralateral PY and substantia nigra (SN) changes following ICH as demonstrated in several other ICH animal model studies can be secondary to use of different ICH sites and different imaging time points in those studies (23, 43, 46, 49). In their study they employ a robust rodent ICH model utilizing intra-striatal collagenase infusion to create the hematoma (50). They then longitudinally quantitatively assessed the changes on DTI in both contralateral and ipsilateral SN and PY tracts following ICH which were compared with histological examination.…”
Section: Existing Evidence For Dti Application In Hemorrhagic Strokementioning
confidence: 99%